HUBUNGAN TINGKAT PENDIDIKAN FORMAL DAN PENGETAHUAN IBU DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA ANAK USIA 0-59 BULAN DI KELURAHAN BUMIJO KECAMATAN JETIS KOTA YOGYAKARTA - Dewi Ariyani Wulandari; Prastiwi Putri Basuki (STIKES Wira Husada Yogyakarta, 2019)
Infants and toddlers are group of people who are vulnerable to various diseases, especially infectious diseases of Acute Respiratory Infection (ARI). ARI is a disease that causes the highest morbidity and mortality in poor and developing countries. A good knowledge and understanding of a mother who has a toddler are important thing related to the risk factors for ARI. This study aims to analyze the relationship between formal education level and mother's knowledge with the incidence of ARI in children aged 0-59 months in Bumijo Village, Jetis District, Yogyakarta City. This research method is an analytic survey with cross sectional research design. The population of this study is mothers who have children aged 0-59 months in the village of Bumijo. The sampling technique was proportionate stratified random sampling technique with 89 mothers. Data analysis was using univariate and bivariate. Spearman rank test results indicate that there is a level of formal education of mothers with ARI events (p = 0.031) with the strength of a strong relationship (r = 0.612). There is a level of maternal knowledge with the incidence of ARI (p = 0,000) with the strength of a strong relationship (r = 0.505). Recomendation of this research are the Public Heath Center to improve health education related to ARI in infants with informative media and mothers to implement ARI’s prevention in toddlers with clean and healthy life